EFFECT OF LEAD ON IMMUNOLOGICAL INDICATORS OF LAYING HENS - Серветник, Н. Р. (Scientific Progress & Innovations, 2014)
This paper presents the results of research on the impact of feeding different doses of lead acetate on immunological parameters of laying hens. Established that the insertion into the organism of chickens lead ions in amounts of 2.5, 5 and 12.5 mg / kg body weight for 45 days caused a probable increase in the concentration of circulating immune complexes in the serum of birds of all experimental groups compared to controls. Also in laying hens research groups have observed a tendency to increase the degree of endogenous intoxication, as evidenced by an increase in serum content of medium molecules.